Analysis of Parenting Patterns to Improve Children's Psychosocial Development: Systematic Review - Tisnawati; Delima; Herwati (POLTEKKES KEMENKES PADANG, 2024)
Parenting styles play a very important role in children's psychosocial development. Psychosocial development is personality development related to behavioral and social relationships. Psychosocial development has stages, and each stage has a critical period or a developmental task that must be passed. This is where the role of the family is needed as the first educator, in creating good psychosocial development. This research aims to develop parenting patterns to improve children's psychosocial development. The systematic review method is used to search for articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline. The search strategy method uses PRISMA (Preferred Reporting Items for Systematic Review and meta-analysis) through four stages consisting of identification, screening, eligibility, and finally inclusion. The search was limited to publication year (2015 to 2023), article type